2019
DOI: 10.26614/les-wood.2019.v68n02a02
|View full text |Cite
|
Sign up to set email alerts
|

Wood identification using non-destructive confocal laser scanning microscopy

Abstract: Exact wood identification is usually based on observation of wood features under the microscope. For this, we have to take a sample of the wood from the object and cut thin slides, possibly of all three anatomical sections. Such destructive sampling is often not possible on valuable historical objects, and therefore there is a need for non-destructive approaches. The objective of the study is to present the potential of Confocal Laser Scanning Microscopy (CLSM) using an Olympus LEXT OLS5000 for the identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…As previously demonstrated, CLSM enables the recognition of features crucial for wood identification on various objects (Balzano et al, 2019;Čufar et al, 2019), and this study confirms that the method is also useful for identification of charcoal wood without special sample preparation.…”
Section: Discussion and Conclusion Razprava In Zaključkisupporting
confidence: 84%
“…As previously demonstrated, CLSM enables the recognition of features crucial for wood identification on various objects (Balzano et al, 2019;Čufar et al, 2019), and this study confirms that the method is also useful for identification of charcoal wood without special sample preparation.…”
Section: Discussion and Conclusion Razprava In Zaključkisupporting
confidence: 84%
“…Through analysis of the microscopic structure, samples 1 through 4 were the same wood species, identified as willow (Salix spp.) (Sauter and Wellenkamp 1988;Čufar et al 2019;Wagenführ and Wagenführ 2021), as shown in Fig. 3.…”
Section: Microscopic Identificationmentioning
confidence: 87%
“…Figure 12a,b show a normal resin canal with a scalloped section on the observed surface. Because a gradual transition between earlywood and latewood is visible, the species is spruce [45,46].…”
Section: Wood Speciesmentioning
confidence: 99%